Prosodic effects on phrasing: Clash avoidance in Catalan - Prieto, Pilar (2017)
This paper empirically investigates the effects of the presence of stress clash on phrasing decisions in Catalan. An interesting fact about Catalan phrasing, initially noted by Oliva (1992) and also reported by Prieto (2005a), is that the presence of a clash in this language can optionally trigger prosodic restructuring. Five native speakers of Central Catalan read 32 stress-clash and non-stress-clash sentence pairs at normal and fast speech rates, for a total of 320 utterances. The results clearly showthat speakers adjust prosodic phrasing so that clash situations are avoided. Catalan speakers tend to get around stress clash by deleting the first stress in the clash and grouping the two words into one phonological phrase, thus avoiding potential prosodic breaks between the two words. This shows that the phonological construction of phonological phrases cannot rely exclusively on syntactic information, but rather that metrical structure needs to be accessible. All in all, this article offers empirical support for one of the predictions of metrical phonology, namely that languages tend to alternate between metrically strong and weak syllables and that stress clash situations are avoided crosslinguistically.